Knowledge Economy and Financial Sector Competition in African Countries - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
The goal of this paper is to assess how knowledge economy (KE) plays out in financial sector competition. It suggests a practicable way to disentangle the effects of different components of KE on various financial sectors. The variables identified under the World Bank's four knowledge economy index (KEI) are employed. An endogeneity robust panel instrumental variable fixed-effects estimation strategy is employed on data from 53 African countries for the period 1996-2010. The following findings are established. First, education and innovation in terms of scientific and technical publications broadly bear an inverse nexus with financial development. Second, the incidence of information and communication technologies is positive on all financial sectors but increases the non-formal sectors to the detriment of the formal sector. Third, economic incentives have positive implications for all sectors though the formal financial sector benefits most. Fourth, institutional regime is positive (negative) for the semi-formal (informal) financial sector. The findings contribute at the same time to the macroeconomic literature on measuring financial development and respond to the growing fields of informal sector importance, microfinance and mobile banking by means of KE promotion. Policy implications and future research directions are discussed.
Keywords: G21; O10; O34; P00; P48; 330; Financial development; Knowledge Economy; Africa